ACHIEVEMENTS AND PROSPECTS OF CROSS-DISCIPLINARY APPROACH TO TUBERCULOSIS CONTROL AS A MULTI-ORGAN AND COMORBID PATHOLOGY IN MOLDOVA REPUBLIC - K. M. Yavorskiy; E. M. Tudor; V. A. Bolotnikova; A. F. Moskovchuk; A. G. Brumaru; S. M. Aleksandru (Туберкулез и болезни лёгких, 2016)
Despite that the turning point was achieved in tuberculosis control in the world, still there is on-going interest to this social disease.Goal: to evaluate changes of main epidemiological rates, to publish achievements and prospects of the implementation of National tuberculosis control programme for the period after 2015.Materials and methods. Comparative analysis included evolution of tuberculosis in various localizations in 2011-2015.Results. Tuberculosis situation has been gradually improving in the Republic of Moldova for the last 5 years. The data evidence about the number of tuberculosis cases going down but the global burden of the disease remains fairly high. The success in tuberculosis control supported by WHO and other international organizations is also related to certain Moldavian research achievements.Conclusion. Due to diversity of clinical forms of tuberculosis and the growing problem of comorbidity the cross-disciplinary approach to tuberculosis control can assure success of these activities.